THE RENAL CELL TUMORS- NEW CLASSIFICATION ACCORDING TO THE WORLD HEALTH ORGANISATION (2022) - Nikolic, Gorana; Pekmezovic, Tatjana; Radojevic Skodric, Sanja (Medicinski podmladak, 2023)
The fifth edition of the World Health Organization’s classification of urogenital tumors, published in 2022, includes significant revisions regarding the classification of kidney cancer. In addition to the basic subsections for each type of kidney cancer, such as epidemiology, etiology, macroscopic and microscopic descriptions, and genetic research, a subsection called "Essential and Desired Diagnostic Criteria" has been included in the fifth edition of the WHO, which represents morphological diagnostic criteria combined with immunohistochemistry and relevant molecular tests. The global introduction of massive parallel sequencing will result in a diagnostic shift from morphology to molecular analysis. Therefore, a molecularly guided Classification of kidney tumors has been introduced, taking into account recent discoveries in renal tumor genomics. Such newly molecularly defined epithelial kidney tumors include SMARCB1-deficient medullary renal cell carcinoma (RCC), TFEB-altered RCC, ALK-rearranged RCC, and ELOC-mutated RCC. Eosinophilic solid and cystic RCC is a new morphologically defined RCC entity primarily characterized by immunohistochemical positivity for CD20. Considering that kidney cancers are resistant to chemotherapy and radiation therapy, immunotherapy has been introduced for RCCs with detected mutations and has shown promising results and therapeutic response. For this reason, it is necessary to incorporate molecular testing into standard routine diagnostics in order to initiate immunotherapy for patients, thereby improving quality of life and extending overall survival.